Development of an Attitude Scale Towards Art-Integrated Social Studies Course - Çakır, Canan; Kahveci, Nihat Gürel (Journal of History Culture and Art Research, 2023)
This study aims to develop a valid and reliable scale for determining the attitudes of gifted individuals towards the art-integrated social studies course. The sample of the study consists of a total of 350 academically gifted students at the 5th-grade level who responded to the measurement tool during the second semester of the 2021-2022 academic year in Science and Art Centers (SAC) [Bilim ve Sanat Merkezi, (BILSEM) in Turkish] in two central districts of Istanbul, one on the Anatolian side and the other on the European side. Evidence regarding the psychometric properties of the scale form was obtained through the analyses conducted on the validity and reliability of the data obtained from the sample to determine the scale’s construct validity. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed on the entire dataset obtained from the study group to determine the scale’s construct validity. As a result of the Exploratory Factor Analysis (EFA), a scale consisting of 50 items and three sub-dimensions was obtained. Based on the judgments reflected by the scale items, the sub-dimensions of the scale were named "attitude towards art-integrated social studies course", "attitude towards art", and "attitude towards social studies course". The three-factor structure of the scale explains 43.45% of the total variance. CFA results revealed that this three-factor structure shows acceptable fit values [(χ2 /sd= 2.26, RMSEA=0.06, S-RMR=0.06, GFI=0.76, AGFI=0.73, CFI=0.90)]. To determine the reliability of the scale, the calculated Cronbach Alpha internal consistency coefficient is "0.95" for the whole scale and .95, .88, and .84 for the sub-factors, respectively. The findings indicate that the scale is a valid and reliable measurement tool for determining attitudes towards art-integrated social studies courses.